The Role of Academic Supervision in Enhancing Teachers’ Pedagogical Competence: A Case Study of South Aceh - Satria, Heri; Niswanto, Niswanto; Ismail, Ismail (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the role of academic supervision in enhancing teachers' pedagogical competence in South Aceh, focusing on the supervision practices of school principals and their impact on teacher development. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis from six participants, including school principals, vice principals, and senior teachers. The findings reveal that effective academic supervision contributes to significant improvements in teaching practices, particularly when feedback and follow-up mechanisms are well-structured. Key themes emerging from the data include supervision planning, pedagogical improvement, challenges in supervision, and follow-up practices. However, the study also highlights several challenges, including time constraints, lack of resources, and insufficient training for principals, which hinder the effectiveness of supervision. Additionally, technological limitations in rural schools exacerbate these challenges. Despite these barriers, participants emphasized the importance of continuous supervision and personalized feedback in driving teacher improvement. This research contributes to the understanding of academic supervision in resource-limited settings, offering practical recommendations for improving the supervision process. These include enhanced training for school leaders, better resource allocation, and the integration of technology into the supervision process. Future research should explore long-term impacts of supervision on teaching outcomes and strategies for overcoming the identified challenges in broader educational contexts.